Tradisi Assuro Maca dalam Masyarakat di Kabupaten Gowa; Analisis Hukum Islam - Ibrahim Ibrahim; Zulhas’ari Mustafa (Universitas Islam Negeri Alauddin Makassar, 2021)
The main problem of this research is how is the process of acculturation between Assuro Maca and the teachings of Islamic law? What is the process of implementing Assuro Maca in Tanakaraeng Village? How do people view the Assuro Maca tradition? The type of research used is field research or Field Research, namely the author conducts research directly to the location and at the same time the researcher is directly involved with the object studied in the study, this type of research is descriptive qualitative, namely, the research is intended to understand phenomena or events regarding the traditions carried out by Research subjects produce descriptive data in the form of verbal information from several people who are considered more knowledgeable, as well as the behavior and objects observed. The results of this study indicate that the Assuro Maca tradition is one of a series of events that should not be missed, this is a tradition that cannot be denied that it is a cultural product created by Muslims themselves, while the others have no clear origin but all of them. rooted in Islam. This event is carried out as a form of gratitude to Allah SWT for His grace and blessings so that our sustenance will be smooth and never broken, and that's why this tradition also encourages prayer and asks for protection and safety in the world in the hereafter. The implication of this research is to explain the cultural values contained in the process of the Assuro Maca tradition to the people in the village of Tanakaraeng ke. Manuju District. Gowa